PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP LITERASI SAINS PESERTA DIDIK KELAS VA SDN 02 BEJEN KECAMATAN KARANGANYAR TAHUN PELAJARAN 2024/2025 - Septianingrum, Devi; Grahito Wicaksono, Anggit; Jumanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examined the effect of the RADEC model (Read, Answer, Discuss, Explain, and Create) on science literacy among fifth-grade students at SD Negeri 02 Bejen, Karanganyar, during the 2024/2025 academic year. A quantitative approach with a one-group pretest–posttest quasi-experimental design was employed, involving 31 students. Data were collected through multiple-choice tests, observations, and documentation. The instrument, tested for validity and reliability, consisted of 20 valid items with a reliability coefficient of 0.879. Data analysis included the Shapiro–Wilk normality test and Paired Sample t-test. Results indicated an increase in the mean score from 65.65 in the pretest to 82.42 in the posttest, with t_calculated = 18.347 exceeding t_table = 2.042 at a 5% significance level, leading to the rejection of H0. These findings confirm that RADEC significantly enhances students’ science literacy and supports science learning in primary education by fostering conceptual understanding, scientific thinking skills, and academic achievement.